THE EFFECT OF SYNTHESIS STEP AND HEATING TEMPERATURE ON SYNTHESIS OF MATERIALS CH3NH3PbI3 - Ari Safitri; Cahyorini Kusumawardani (Jurnal Elemen Kimia, 2018)
AbstractResearch on the effeect of one-step and two-step methods on the electronicstructure and character of perovskite material CH3NH3PbI3 has been carried out, aswell as the effect of temperature variations on the perovskite material CH3NH3PbI3.Synthesis with one-step method was carried out by dissolving PbI2 in DMF (taken byfiltrate) and dissolving CH3NH3I in isopropanol then the filtrate and CH3NH3Isolutions were mixed and stirring was carried out. After the two mixed solutions arethen coated on a glass substrate that has been coated with compact-TiO2 dan m-TiO2,heating on the hotplate at 130°C for 15 minutes. The two-step method was carriedout by dissolving PbI2 in DMF (taken by filtrate), then coating it on a glass substrate,then dissolving CH3NH3I in isopropanol and overlaying PbI2 then heated on ahotplate at 130°C for 15 minutes. Optimal temperature determination is carried outaccording to the one-step synthesis, heating temperature above the hotplate 100°C,110°C, 130°C, and 150°C. The synthesis material was then characterized using XRDand UV-Vis.The XRD characterization results showed that CH3NH3PbI3 materialsynthesized in one step and two stages had an effect on the crystal size of 29.0567 nmand 22.60172 nm, while for amorphous crystal structure temperature variations. Theresults of UV-Vis analysis result obtained absorbance data and band gap energy.One-step synthesis method produces a maximum absorbance of 745 nm, a synthesismethod of two-step 733 nm, for the maximum temperature variation of absorbancedata at 100°C, 110°C, 130°C, and 150°C is 585 nm, 585 nm, 481 nm, and 484 nm.Band gap energy has an effect on the synthesis of CH3NH3PbI3 material with onestepand two-step. In the one-step synthesis method, the band gap energy is 1.543 eVand the two-step synthesis method obtained 1.614 eV, while for temperature variationproduces 2.67 eV to 3.74eV.Keywords: CH3NH3PbI3, One-Step, Two-Step, Temperature Variation